SELF EFFICACY SISWA TUNADAKSA DI SD NEGERI SIRNASARI - Linda Ariesandi; Nenden Ineu Herawati (STKIP Subang, 2023)
This study aims to describe the self-efficacy of students with disabilities in SDNegeri Sirnasari. Self-efficacy in students with disabilities can be seen through 3 dimensions, namely the level of difficulty (Level), the level of confidence (strength), and generalization (generality). This research is qualitative research with a type of case study research. The subject of this study was one student with disabilities. The informants in this study were grade II teachers, PAI teachers, health care teachers, dance teachers, parents of students with disabilities, caregivers of students with disabilities, and representatives of classmates of students with disabilities. The object in this study is self-efficacy. The data collection used are observation, interviews, and documentation studies. Data analysis uses data reduction, display, and inference. Test the validity of the data using source triangulation and triangulation techniques. Based on the results of self-efficacy research on students with disabilities at SDNegeri Sirnasari with the initials AR, results were obtained that showed that the self-efficacy possessed by students with disabilities seemed to vary in each dimension of the aspects studied in this study.